Two new Halamphora (Bacillariophyta) species and the first fossil observations for Halamphora elongata in holocene lacustrine deposits of Hassi Manda in the Erg Er Raoui (Algerian Sahara Desert) - Hamadai, Ali; Hamilton, Paul Brian; Bouhameur, Mansour; Mennad, Saci; Saber, Abdullah A.; Ertorun, Nesil; Sahraoui, Boutheina; Solak, Cüneyt Nadir (Phytotaxa, 2026)
This paper describes two new species of Halamphora—Halamphora mujdatiana sp. nov., H. tabelbalaensis sp. nov. and records for the first time Halamphora elongata from fossil deposits in the Algerian Sahara Desert. The study utilized light and scanning electron microscopy to examine valve morphology. These species were found in Holocene lacustrine deposits of Hassi Manda in the Erg Er Raoui. The newly identified species, H. mujdatiana is characterized by larger rounded areolae towards to margin while smaller areolae in the central area with a very narrow raphe ledge. Additionally, ventral striae on the external face are composed of biseriate areolae in the central area and uniseriate areolae towards to the apices. Halamphora tabelbalaensis is distinguished by long elongated areolae on the striae and uniseriate areolae at the apices.